2023
DOI: 10.1017/s2045796023000586
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder among LGBTQ people: a systematic review and meta-analysis

Abstract: Aims Lesbian, gay, bisexual, transgender and queer people (LGBTQ) are at increased risk of traumatization. This systematic review aimed to summarize data regarding the risk of post-traumatic stress disorder (PTSD) for LGBTQ people and their subgroups. Methods Medline, Scopus, PsycINFO and EMBASE were searched until September 2022. Studies reporting a comparative estimation of PTSD among LGBTQ population and the general population (i.e., heterosexual/cisgender), without restrictions on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…This is particularly important to the study of PTSD, which in the general population is more common amongst women (Olff, 2017). Additionally, research shows that transgender people are at the high risk of PTSD (Marchi et al, 2023;Reisner et al, 2016). A large population study showed higher numbers of transgender and gender diverse people are autistic when compared to cisgender people (Warrier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important to the study of PTSD, which in the general population is more common amongst women (Olff, 2017). Additionally, research shows that transgender people are at the high risk of PTSD (Marchi et al, 2023;Reisner et al, 2016). A large population study showed higher numbers of transgender and gender diverse people are autistic when compared to cisgender people (Warrier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, masculine gender role stress (Neilson et al, 2020) or hormonal changes related to androgen deprivation therapy in the context of prostate cancer (Donovan et al, 2015) might be interesting targets to increase knowledge on men-specific risk factors. Moreover, a nonbinary perspective on sex and gender can help to address existing data gaps and improve care for currently underserved high-risk communities (Marchi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many studies found the prevalence of both PTSD and CPTSD to be about twice as high in women as in men (Cloitre et al, 2019 ; Driessen et al, 2008 ; Hyland, Murphy, et al, 2017 ; Tolin & Foa, 2006 ). The risk of developing PTSD among LGBTQ people is even higher, especially for transgender people, since due to transphobia/homophobia individuals within sexual minority groups continue to face a heightened risk of experiencing trauma including childhood abuse (Marchi et al, 2023 ; Roberts et al, 2012 ). Nevertheless, there are conflicting findings in studies; some report a sex-specific risk for PTSD but not for CPTSD (Hyland, Shevlin, et al, 2017 ; McGinty et al, 2021 ), while others found this neither for PTSD nor for CPTSD (Cloitre et al, 2013 ; Wolf et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%